1985
DOI: 10.1136/vr.116.3.69
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of dead Ostertagia ostertagi in the abomasal mucosa following anthelmintic treatment

Abstract: Anthelmintic trails, conducted with albendazole, fenbendazole and ivermectin for efficacy against gastrointestinal nematodes, principally inhibited early fourth larval stages of Ostertagia ostertagi in naturally infected cattle. Cattle wee slaughtered seven to 20 days after treatment. O ostertagi was the predominant abomasal nematode recovered with occasional small numbers of Haemonchus species and Trichostrongylus axei. Control calves uniformly had very large O ostertagi infections, primarily early fourth sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Clinically, the lesions may present as purpuric eruptions or linear streaks associated with cutaneous invasion by the larvae. The histological diagnosis is based on the identification of the cross and oblique sections of S. stercoralis in the dermis associated with RBCs extravasation and occasional Splendore‐Hoeppli reaction 58,59 …”
Section: Mucocutaneous Infections Associated With Splendore‐hoeppli Pmentioning
confidence: 99%
“…Clinically, the lesions may present as purpuric eruptions or linear streaks associated with cutaneous invasion by the larvae. The histological diagnosis is based on the identification of the cross and oblique sections of S. stercoralis in the dermis associated with RBCs extravasation and occasional Splendore‐Hoeppli reaction 58,59 …”
Section: Mucocutaneous Infections Associated With Splendore‐hoeppli Pmentioning
confidence: 99%
“…(i) In yearling beef cattle naturally infected with O . ostertagi , treated with fenbendazole while a large number of early fourth stage inhibited larvae had been established, and then slaughtered 7 to 12 days after treatment, Snider III et al (1985) [ 62 ] observed an aggravation of the abomasal inflammatory lesions compared to those found in untreated calves. This aggravation was related to the persistence of dead and degenerate O .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these degenerate larvae were not observed in the tissues of untreated calves nor in calves treated with ivermectin, and were thus attributed to the fenbendazole treatment. Histologically, the presence of a marked eosinophil and lymphocyte infiltration and of an unidentified material coating the degenerate larvae suggested an inflammatory and/or immunological response initiated or exacerbated by the presence of such larvae [ 62 ]. (ii) Similar results were found in horses naturally infected with cyathostomins and treated either with fenbendazole or moxidectin [ 63 ]: in contrast to moxidectin effects, the killing of larvae due to fenbendazole treatment was associated with severe tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation